EVEKTIFITAS MODEL PEMBELAJARAN BERBASIS PROYEK (PROJECT-BASED LEARNING) DALAM MENINGKATKAN KETRAMPILAN ABAD KE-21 SISWA MADRASAH IBTIDAIYAH - Cahyani, Eri Latri; Ningsih, Dwi Setya; Khamidah, Lailatul; Latifah, Umul; Maulandari, Siti Diajeng Meva; Suttrisno, Suttrisno (STKIP Pesisir Selatan, 2025)
PJBL plays a role in the learning process in Madrasah Ibtidaiyah and provides recommendations for the development of more effective learning strategies, in accordance with the demands of the Merdeka Curriculum and the Pancasila Student Profile. PBL not only deepens understanding of concepts, but also functions to train critical thinking, creativity, communication, and collaboration skills in a practical and contextual way. This study aims to explore the extent to which a project-focused teaching model (Project-Based Learning/PjBL) can improve 21st-century skills, especially in the aspects of creativity, communication, collaboration, critical thinking, and problem-solving skills in Madrasah Ibtidaiyah students. The approach used is a literature study by analyzing scientific works from both national and international journals. The results of the study show that the application of the PjBL model significantly increases creativity, problem-solving skills, and student learning outcomes in thematic learning. In addition, PjBL provides a contextual and real-life learning experience. This study recommends the implementation of PjBL as an innovative learning strategy at the elementary level in order to develop student competencies that are able to adapt to the challenges of the 21st century.